A History of Australian Co-operatives 1827–2023 - Patmore, Greg (Taylor & Francis, 2024)
Co-operatives provide a different approach to organising business through their ideals of member ownership and democratic practice. Every co-operative member has an equal vote regardless of his or her own personal capital investment. They take a variety of different forms, including consumer co-operatives, agricultural co-operatives, worker co-operatives and financial co-operatives.